Women at work. An economic perspective - Boeri, Tito; Del Boca, Daniela; Pissarides, Christopher A. (New York, 2005)
"Covering employment and wage gender gaps, the participation of women, fertility, and the welfare of children, this volume discusses how the trend towards greater participation of women in labor markets interacts with gender differences in pay. It focuses on the increasing the number of women in the labor force without negatively affecting the development of their children. "